MAP3K kinases and kidney injury - Cuarental, Leticia; Sucunza-Sáenz, David; Valino-Rivas, Lara; Fernandez-Fernandez, Beatriz; Sanz, Ana Belén; Ortiz, Alberto; Vaquero, Juan José; Sanchez-Nino, Maria Dolores (Sociedad Española de Nefrología, 2019)
Mitogen-activated protein kinases (MAP kinases) are functionally connected kinases that regulate key cellular process involved in kidney disease such as all survival, death, differ entiation and proliferation. The typical MAP kinase module is composed by a cascade of three kinases: a MAP kinase kinase kinase (MAP3K) that phosphorylates and activates a MAP kinase kinase (MAP2K) which phosphorylates a MAP kinase (MAPK). While the role of MAPKs such as ERK, p38 and JNK has been well characterized in experimental kidney injury, much less is known about the apical kinases in the cascade, the MAP3Ks. There are 24 characterized MAP3K (MAP3K1 to MAP3K21 plus RAF1, BRAF and ARAF). We now review current knowledge on the involvement of MAP3K in non-malignant kidney disease and the therapeutic tools available. There is in vivo interventional evidence clearly supporting a role for MAP3K5 (ASK1) and MAP3K14 (NIK) in the pathogenesis of experimental kidney disease. Indeed, the ASK1 inhibitor Selonsertib has undergone clinical trials for diabetic kidney dis ease. Additionally, although MAP3K7 (MEKK7, TAK1) is required for kidney development, acutely targeting MAP3K7 protected from acute and chronic kidney injury; and targeting MAP3K8 (TPL2/Cot) protected from acute kidney injury. By contrast MAP3K15 (ASK3) may protect from hypertension and BRAF inhibitors in clinical use may induced acute kidney injury and nephrotic syndrome. Given their role as upstream regulators of intracellular sig naling, MAP3K are potential therapeutic targets in kidney injury, as demonstrated for some of them. However, the role of most MAP3K in kidney disease remains unexploredMitogen-activated protein kinases (MAP kinases) are functionally connected kinases that regulate key cellular process involved in kidney disease such as all survival, death, differ entiation and proliferation. The typical MAP kinase module is composed by a cascade of three kinases: a MAP kinase kinase kinase (MAP3K) that phosphorylates and activates a MAP kinase kinase (MAP2K) which phosphorylates a MAP kinase (MAPK). While the role of MAPKs such as ERK, p38 and JNK has been well characterized in experimental kidney injury, much less is known about the apical kinases in the cascade, the MAP3Ks. There are 24 characterized MAP3K (MAP3K1 to MAP3K21 plus RAF1, BRAF and ARAF). We now review current knowledge on the involvement of MAP3K in non-malignant kidney disease and the therapeutic tools available. There is in vivo interventional evidence clearly supporting a role for MAP3K5 (ASK1) and MAP3K14 (NIK) in the pathogenesis of experimental kidney disease. Indeed, the ASK1 inhibitor Selonsertib has undergone clinical trials for diabetic kidney dis ease. Additionally, although MAP3K7 (MEKK7, TAK1) is required for kidney development, acutely targeting MAP3K7 protected from acute and chronic kidney injury; and targeting MAP3K8 (TPL2/Cot) protected from acute kidney injury. By contrast MAP3K15 (ASK3) may protect from hypertension and BRAF inhibitors in clinical use may induced acute kidney injury and nephrotic syndrome. Given their role as upstream regulators of intracellular sig naling, MAP3K are potential therapeutic targets in kidney injury, as demonstrated for some of them. However, the role of most MAP3K in kidney disease remains unexplored